Variable and Conserved Regions of Secondary Structure in the β-Trefoil Fold: Structure Versus Function - Blaber, Michael (Frontiers in Molecular Biosciences, 2022)
β-trefoil proteins exhibit an approximate C3 rotational symmetry. An analysis of the secondary structure for members of this diverse superfamily of proteins indicates that it is comprised of remarkably conserved β-strands and highly-divergent turn regions. A fundamental "minimal" architecture can be identified that is devoid of heterogenous and extended turn regions, and is conserved among all family members. Conversely, the different functional families of β-trefoils can potentially be identified by their unique turn patterns (or turn "signature"). Such analyses provide clues as to the evolution of the β-trefoil family, suggesting a folding/stability role for the β-strands and a functional role for turn regions. This viewpoint can also guide de novo protein design of β-trefoil proteins having novel functionality.